Room-temperature spin injection and optical polarization in nitride-based blue and ultra-violet spin light-emitting diodes. (11th November 2020) - Wu, Yaping; Wu, Xuefeng; Zhong, Zhibai; Zhou, Jiangpeng; Chen, Jiajun; Guo, Jian; Song, Anke; Li, Xu; Wu, Zhiming; Kang, Junyong
Abstract: RT spin injection and optical polarization in nitride-based spin-LEDs are investigated. By employing CoFeB/MgO as the spin injector, the spin relaxation time and diffusion length in n-type GaN film are revealed to be 54.9 ps and 214.4 nm, respectively, through the three-terminal Hanle measurement. As the spin injector structure is applied to blue spin-LED, a maximal circular polarization of 3.3% is detected in electroluminescence, with the surface-emitting geometry and under a vertical magnetic field. UV spin-LED with n-Al0.05 Ga0.95 N transport layer is also fabricated, whose optical polarization is relatively smaller due to the larger spin–orbit coupling in Al atoms.